Number 10 (December 1980) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1980)
New Records for the Northern Studfish Fundulus catenatus, in the Lower Mississippi and Gulf Coastal Drainages. By H.L. Bart and R.C. Cashner, plus News Notes, 5 pp.
Keywords: fishes; northern studfish; fundulus catenatus